# The Applicative Contract

Just like Functor, Monad, and types that implement BEq and Hashable, Applicative has a set of rules that all instances should adhere to.

There are four rules that an applicative functor should follow:

1. It should respect identity, so pure id <*> v = v
2. It should respect function composition, so pure (· ∘ ·) <*> u <*> v <*> w = u <*> (v <*> w)
3. Sequencing pure operations should be a no-op, so pure f <*> pure x = pure (f x)
4. The ordering of pure operations doesn't matter, so u <*> pure x = pure (fun f => f x) <*> u

To check these for the Applicative Option instance, start by expanding pure into some.

The first rule states that some id <*> v = v. The definition of seq for Option states that this is the same as id <$> v = v, which is one of the Functor rules that have already been checked. The second rule states that some (· ∘ ·) <*> u <*> v <*> w = u <*> (v <*> w). If any of u, v, or w is none, then both sides are none, so the property holds. Assuming that u is some f, that v is some g, and that w is some x, then this is equivalent to saying that some (· ∘ ·) <*> some f <*> some g <*> some x = some f <*> (some g <*> some x). Evaluating the two sides yields the same result: some (· ∘ ·) <*> some f <*> some g <*> some x ===> some (f ∘ ·) <*> some g <*> some x ===> some (f ∘ g) <*> some x ===> some ((f ∘ g) x) ===> some (f (g x)) some f <*> (some g <*> some x) ===> some f <*> (some (g x)) ===> some (f (g x))  The third rule follows directly from the definition of seq: some f <*> some x ===> f <$> some x
===>
some (f x)


In the fourth case, assume that u is some f, because if it's none, both sides of the equation are none. some f <*> some x evaluates directly to some (f x), as does some (fun g => g x) <*> some f.

## All Applicatives are Functors

The two operators for Applicative are enough to define map:

def map [Applicative f] (g : α → β) (x : f α) : f β :=
pure g <*> x


This can only be used to implement Functor if the contract for Applicative guarantees the contract for Functor, however. The first rule of Functor is that id <$> x = x, which follows directly from the first rule for Applicative. The second rule of Functor is that map (f ∘ g) x = map f (map g x). Unfolding the definition of map here results in pure (f ∘ g) <*> x = pure f <*> (pure g <*> x). Using the rule that sequencing pure operations is a no-op, the left side can be rewritten to pure (· ∘ ·) <*> pure f <*> pure g <*> x. This is an instance of the rule that states that applicative functors respect function composition. This justifies a definition of Applicative that extends Functor, with a default definition of map given in terms of pure and seq: class Applicative (f : Type → Type) extends Functor f where pure : α → f α seq : f (α → β) → (Unit → f α) → f β map g x := seq (pure g) (fun () => x)  ## All Monads are Applicative Functors An instance of Monad already requires an implementation of pure. Together with bind, this is enough to define seq: def seq [Monad m] (f : m (α → β)) (x : Unit → m α) : m β := do let g ← f let y ← x () pure (g y)  Once again, checking that the Monad contract implies the Applicative contract will allow this to be used as a default definition for seq if Monad extends Applicative. The rest of this section consists of an argument that this implementation of seq based on bind in fact satisfies the Applicative contract. One of the beautiful things about functional programming is that this kind of argument can be worked out on a piece of paper with a pencil, using the kinds of evaluation rules from the initial section on evaluating expressions. Thinking about the meanings of the operations while reading these arguments can sometimes help with understanding. Replacing do-notation with explicit uses of >>= makes it easier to apply the Monad rules: def seq [Monad m] (f : m (α → β)) (x : Unit → m α) : m β := do f >>= fun g => x () >>= fun y => pure (g y)  To check that this definition respects identity, check that seq (pure id) (fun () => v) = v. The left hand side is equivalent to pure id >>= fun g => (fun () => v) () >>= fun y => pure (g y). The unit function in the middle can be eliminated immediately, yielding pure id >>= fun g => v >>= fun y => pure (g y). Using the fact that pure is a left identity of >>=, this is the same as v >>= fun y => pure (id y), which is v >>= fun y => pure y. Because fun x => f x is the same as f, this is the same as v >>= pure, and the fact that pure is a right identity of >>= can be used to get v. This kind of informal reasoning can be made easier to read with a bit of reformatting. In the following chart, read "EXPR1 ={ REASON }= EXPR2" as "EXPR1 is the same as EXPR2 because REASON": pure id >>= fun g => v >>= fun y => pure (g y) ={ pure is a left identity of >>= }= v >>= fun y => pure (id y) ={ Reduce the call to id }= v >>= fun y => pure y ={ fun x => f x is the same as f }= v >>= pure ={ pure is a right identity of >>= }= v To check that it respects function composition, check that pure (· ∘ ·) <*> u <*> v <*> w = u <*> (v <*> w). The first step is to replace <*> with this definition of seq. After that, a (somewhat long) series of steps that use the identity and associativity rules from the Monad contract is enough to get from one to the other: seq (seq (seq (pure (· ∘ ·)) (fun _ => u)) (fun _ => v)) (fun _ => w) ={ Definition of seq }= ((pure (· ∘ ·) >>= fun f => u >>= fun x => pure (f x)) >>= fun g => v >>= fun y => pure (g y)) >>= fun h => w >>= fun z => pure (h z) ={ pure is a left identity of >>= }= ((u >>= fun x => pure (x ∘ ·)) >>= fun g => v >>= fun y => pure (g y)) >>= fun h => w >>= fun z => pure (h z) ={ Insertion of parentheses for clarity }= ((u >>= fun x => pure (x ∘ ·)) >>= (fun g => v >>= fun y => pure (g y))) >>= fun h => w >>= fun z => pure (h z) ={ Associativity of >>= }= (u >>= fun x => pure (x ∘ ·) >>= fun g => v >>= fun y => pure (g y)) >>= fun h => w >>= fun z => pure (h z) ={ pure is a left identity of >>= }= (u >>= fun x => v >>= fun y => pure (x ∘ y)) >>= fun h => w >>= fun z => pure (h z) ={ Associativity of >>= }= u >>= fun x => v >>= fun y => pure (x ∘ y) >>= fun h => w >>= fun z => pure (h z) ={ pure is a left identity of >>= }= u >>= fun x => v >>= fun y => w >>= fun z => pure ((x ∘ y) z) ={ Definition of function composition }= u >>= fun x => v >>= fun y => w >>= fun z => pure (x (y z)) ={ Time to start moving backwards!pure is a left identity of >>= }= u >>= fun x => v >>= fun y => w >>= fun z => pure (y z) >>= fun q => pure (x q) ={ Associativity of >>= }= u >>= fun x => v >>= fun y => (w >>= fun p => pure (y p)) >>= fun q => pure (x q) ={ Associativity of >>= }= u >>= fun x => (v >>= fun y => w >>= fun q => pure (y q)) >>= fun z => pure (x z) ={ This includes the definition of seq }= u >>= fun x => seq v (fun () => w) >>= fun q => pure (x q) ={ This also includes the definition of seq }= seq u (fun () => seq v (fun () => w)) To check that sequencing pure operations is a no-op: seq (pure f) (fun () => pure x) ={ Replacing seq with its definition }= pure f >>= fun g => pure x >>= fun y => pure (g y) ={ pure is a left identity of >>= }= pure f >>= fun g => pure (g x) ={ pure is a left identity of >>= }= pure (f x) And finally, to check that the ordering of pure operations doesn't matter: seq u (fun () => pure x) ={ Definition of seq }= u >>= fun f => pure x >>= fun y => pure (f y) ={ pure is a left identity of >>= }= u >>= fun f => pure (f x) ={ Clever replacement of one expression by an equivalent one that makes the rule match }= u >>= fun f => pure ((fun g => g x) f) ={ pure is a left identity of >>= }= pure (fun g => g x) >>= fun h => u >>= fun f => pure (h f) ={ Definition of seq }= seq (pure (fun f => f x)) (fun () => u) This justifies a definition of Monad that extends Applicative, with a default definition of seq: class Monad (m : Type → Type) extends Applicative m where bind : m α → (α → m β) → m β seq f x := bind f fun g => bind (x ()) fun y => pure (g y)  Applicative's own default definition of map means that every Monad instance automatically generates Applicative and Functor instances as well. ## Additional Stipulations In addition to adhering to the individual contracts associated with each type class, combined implementations Functor, Applicative and Monad should work equivalently to these default implementations. In other words, a type that provides both Applicative and Monad instances should not have an implementation of seq that works differently from the version that the Monad instance generates as a default implementation. This is important because polymorphic functions may be refactored to replace a use of >>= with an equivalent use of <*>, or a use of <*> with an equivalent use of >>=. This refactoring should not change the meaning of programs that use this code. This rule explains why Validate.andThen should not be used to implement bind in a Monad instance. On its own, it obeys the monad contract. However, when it is used to implement seq, the behavior is not equivalent to seq itself. To see where they differ, take the example of two computations, both of which return errors. Start with an example of a case where two errors should be returned, one from validating a function (which could have just as well resulted from a prior argument to the function), and one from validating an argument: def notFun : Validate String (Nat → String) := .errors { head := "First error", tail := [] } def notArg : Validate String Nat := .errors { head := "Second error", tail := [] }  Combining them with the version of <*> from Validate's Applicative instance results in both errors being reported to the user: notFun <*> notArg ===> match notFun with | .ok g => g <$> notArg
| .errors errs =>
match notArg with
| .ok _ => .errors errs
| .errors errs' => .errors (errs ++ errs')
===>
match notArg with
| .ok _ => .errors { head := "First error", tail := [] }
| .errors errs' => .errors ({ head := "First error", tail := [] } ++ errs')
===>
.errors ({ head := "First error", tail := [] } ++ { head := "Second error", tail := []})
===>
.errors { head := "First error", tail := ["Second error"]}


Using the version of seq that was implemented with >>=, here rewritten to andThen, results in only the first error being available:

seq notFun (fun () => notArg)
===>
notFun.andThen fun g =>
notArg.andThen fun y =>
pure (g y)
===>
match notFun with
| .errors errs => .errors errs
| .ok val =>
(fun g =>
notArg.andThen fun y =>
pure (g y)) val
===>
.errors { head := "First error", tail := [] }